The mediating role of environmental restorativeness between vegetation levels and physical activity intention: a photo-based experimental study - Weng, Shici; Zhang, Xing; Yin, Mingyue; Tian, Haodong; Liu, Haowei; Li, Hansen (Frontiers in Public Health, 2025)
IntroductionVegetation is linked to better health partly by promoting physical activity, but the psychological mechanisms remain unclear. We examined whether perceived environmental restorativeness mediates the association between vegetation level and intention to be physically active.MethodsIn an image-based randomized experiment, Chinese university students viewed simulated outdoor scenes depicting low to high vegetation coverage. After each exposure, participants reported perceived restorativeness (Chinese Perceived Restorativeness Scale; reliability, structural validity, and concurrent validity assessed) and intention to be physically active in the depicted setting. Associations among vegetation level, perceived restorativeness, and intention were tested, and mediation analyses evaluated indirect effects through PRS subscales and the total score.ResultsGreater vegetation coverage was associated with higher perceived restorativeness and stronger intention to engage in physical activity. All PRS subscales significantly mediated the vegetation–intention relationship. The PRS total score showed a full mediation effect, indicating that vegetation influenced physical activity intention largely through perceived restorativeness.DiscussionFindings identify environmental restorativeness as a key psychological pathway linking vegetation to physical activity motivation and suggest that enhancing restorative qualities may be a practical strategy for green-space design to promote activity. Generalizability is limited by the student sample and simulated scenes; future work should recruit more diverse populations and use ecologically valid environments.